2013
DOI: 10.1016/j.amepre.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Food Marketing Expenditures Aimed at Youth

Abstract: In response to concerns about childhood obesity, the Federal Trade Commission (FTC) released two reports documenting food and beverage marketing expenditures to children and adolescents. The recently released 2012 report found an inflation-adjusted 19.5% reduction in marketing expenditures targeted to youth from $2.1 billion in 2006 to $1.8 billion in 2009. The current article highlights features of the FTC’s analysis, examines how expenditures relate to youth exposure to food marketing, and assesses changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 30 publications
4
111
0
1
Order By: Relevance
“…In the US, the Federal Trade Commission reported that total youth-targeted (age 2-7) food marketing expenditures on new media, including corporate websites, advertising on third-party children's websites, marketing via mobile devices, and social media, increased by $45.9 million from 2006 to 2009, totalling $122.5 million (Powell, Harris, & Fox, 2013). While a broader body of work has assessed the impact of this increase in web-based food and beverage marketing on children, only a small number of public health studies have assessed the content and types of marketing aimed at young people through social media platforms.…”
Section: Energy Dense and Nutrient Poor Food And Beveragesmentioning
confidence: 99%
“…In the US, the Federal Trade Commission reported that total youth-targeted (age 2-7) food marketing expenditures on new media, including corporate websites, advertising on third-party children's websites, marketing via mobile devices, and social media, increased by $45.9 million from 2006 to 2009, totalling $122.5 million (Powell, Harris, & Fox, 2013). While a broader body of work has assessed the impact of this increase in web-based food and beverage marketing on children, only a small number of public health studies have assessed the content and types of marketing aimed at young people through social media platforms.…”
Section: Energy Dense and Nutrient Poor Food And Beveragesmentioning
confidence: 99%
“…The ubiquitous promotion of unhealthy food establishes societal norms around acceptable and desirable foods [12,13] and adverts serve as conditioned stimuli that trigger food cravings and cue an increase in food consumption [14], particularly in children [15]. The disparity between food advertising expenditure for different food groups is extreme [13]: government campaigns promoting fruit and vegetables are dwarfed by the billions of dollars spent on fast food and 'junk' food marketing each year [16,17]. The majority of these advertised foods and drinks are high in added fat, sugar and salt, are contrary to dietary recommendations and, if eaten in excess, can contribute to overweight and the risk of developing CVD [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The use of certain negative emotional messages and graphic images in public health campaigns remains controversial (25) , but has been shown to improve message salience and to increase message effectiveness in some contexts (26,27) . Both sufficient exposure and persuasive messaging are crucial, especially given the relative resources and expertise of the food industry in marketing unhealthy products such as those high in saturated fat, sugar and sodium, and with television serving as the dominant platform for such advertising (28)(29)(30)(31) . It is crucial for the public health community to find successful ways to provide counterinformation that might inspire viewers to adopt healthier lifestyles.…”
mentioning
confidence: 99%